Accessing the Influence of Perceived Value on Social Attachment: Developing Country Perspective - Wang, Qingqing; Yang, Maosheng; Zhang, Wensong (Frontiers in Psychology, 2021)
Perceived value has a positive impact on users' social attachment in social media usage contexts and is a topic at the forefront of current research in consumer behavior. Although studies have begun to investigate the factors influencing social attachment, there is a lack of research on how perceived value affects social attachment. Therefore, this study uses privacy concern theory, to build a theoretical model with moderated and mediation roles, using Chinese Tik Tok users as data collection and survey sample, and using Mplus7.0 to analyze the mediation mechanism and boundary conditions of the relationship between perceived value and social attachment through the structural equation model. In Study 1, data were collected from 600 Tik Tok users to verify the mediating role of the sense of belonging in perceived value and social attachment relationship. The users who participated in the questionnaire survey in this study were mainly from mainland China. In Study 2, two waves of data were collected from 500 Tik Tok users, it not only verified the mediating role of the sense of belonging, but also supported part of the moderating role of privacy concerns. However, except that the relationship between information value and social attachment is inhibited by privacy concerns, the relationship between entertainment value and social value and social attachment is not regulated by privacy concerns. This research examines the practical effects of perceived value in the context of social media use, reveals the internal mechanism of the impact of perceived value on social attachment, and provides a reference for the innovative management and commercial practice of local social media.